EARLY DETECTION TRAINING OF HEARING DISORDERS IN THE ERA OF THE COVID 19 PANDEMIC FOR HEALTH PERSONNEL AT GENTENG KULON BANYUWANGI HEALTH CENTER, EAST JAVA - Puguh Setyo Nugroho; Nyilo Purnami; Rizka Fathoni Perdana; Rosa Falerina; Hendra Kurnia Rakhma (Jurnal Layanan Masyarakat (Journal of Public Services), 2022)
The COVID 19 pandemic impacts the early detection of hearing impairment. Socialization is needed in the form of early detection education of hearing loss in the era of the COVID 19 pandemic to health workers in the front line. The purpose of educational activities is to improve the knowledge and skills of health workers to conduct early detection of hearing impairment in the era of the COVID 19 pandemic. The condition of the COVID 19 pandemic changed the interaction pattern between people, including in education and training activities in the field of health. Education with on line means is becoming a common thing to do today. This training activity is conducted on line and off line methods with limited participants. The training for health workers was carried out using an off line method and was attended by 39 participants. The average result of the pre test was 45.20 (+ 15.69), and the average post test was 80.67 (+ 22.73). Comparison of the pre test and post test results with the t-test, the results were significantly different (p < 0.0001). The training with the on line method was attended by 1,145 participants. The results of the average pre test score were 55.30 (+15.61), and the post test average score was 72.82 (+21.61). Comparison of the pre test and post test scores with the t-test results was significantly different (p < 0.0001). On line and off line methods in training activities provide significant results in increasing the knowledge of health workers so that the pandemic does not hinder the implementation of training activities to increase the knowledge of health workers in an effort to improve the quality of life of the community, in this case, hearing.